Gender equality reflected in CSR of key financial insititutions in the Czech Republic - Gluško, Anna (2021)
The main aim of this bachelor thesis is to examine the Corporate Social Responsibility strategy and activities towards gender equality of key financial institutions in the Czech Republic. Further, to evaluate their approach to gender diversity in comparison to their multinational groups. Lastly, to determine whether such policies attract future university graduates as their potential employees. The theoretical part comprises an introduction to the topic of CSR, Sustainable Development Goals and Gender Equality. The practical part examines the three most significant financial institutions in the Czech market, including their international financial groups. The final part is dedicated to a survey among Czech university students to determine their interest in an employer with a gender equality strategy.